Outpatient Outcomes of Pediatric Patients with Left Ventricular Assist Devices. Issue 2 (March 2016) - Chen, Sharon; Lin, Aileen; Liu, Esther; Gowan, Maryalice; May, Lindsay J.; Doan, Lan N.; Almond, Christopher S.; Maeda, Katsuhide; Reinhartz, Olaf; Hollander, Seth A.; Rosenthal, David N.
Abstract : Outpatient experience of children supported with continuous-flow ventricular assist devices (CF-VAD) is limited. We reviewed our experience with children discharged with CF-VAD support. All pediatric patients <18 years old with CF-VADs implanted at our institution were included. Discharge criteria included a stable medication regimen, completion of a VAD education program and standardized rehabilitation plan, and presence of a caregiver. Hospital readmissions (excluding scheduled admissions) were reviewed. Adverse events were defined by Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) criteria. Of 17 patients with CF-VADs, 8 (47%) were discharged from the hospital (1 HeartWare ventricular assist device (Heartware Inc., Framingham, MA), 7 HeartMate II (Thoratec Corp, Pleasanton, CA)). Median age was 15.3 (range 9.6–17.1) years and weight was 50.6 (33.6–141) kg. Device strategies were destination therapy (DT; n = 4) and bridge to transplant (n = 4). Patients spent a median 49 (26–107) days hospitalized postimplant and had 2 (1–5) hospital readmissions. Total support duration was 3, 154 patient-days, with 2, 413 as outpatient. Most frequent adverse events were device malfunction and arrhythmias. There was one death because of pump thrombosis and no bleeding or stroke events. Overall adverse event rate was 15.22 per 100 patient-months. Early experience suggests that children with CF-VADs can be safely discharged. Device malfunction and arrhythmia were the most common adverse events but were recognized quickly with structured outpatient surveillance. Abstract : Supplemental Digital Content is available in the text.